Strategie urbane e rafforzamento identitario nelle nuove periferie al margine della città di Parigi. Il caso studio d’Ivry-sur-Seine - Bartoloni, Tommaso; Martelliano, Vito (SocietàMutamentoPolitica, 2020)
In the context of the progressive and unstoppable increase of the population living in urban suburbs, this paper analyzes the change of perspective by the communities of the first crown of the parisian banlieue who prefer to affirm their local identities rather than being annexed to the metropolis. The relationship between the urban center and the suburbs is complex and has undergone significant changes. If in the years of the building boom the expansions of the major cities included the peripheral centers, today, as a consequence of the urban polycentrism, the urban suburbs recognize to heir own identity and socio-cultural integrity such as to resist metropolitan homologation despite urban expansion and growth. The paper treats this subject starting from the morphological analysis of urban strategies put in place by the local administrations of Paris and Ivry-sur-Seine. In particular, two plans for urban regeneration in continuity are examined, the Bruneseau Nord sector of the ZAC Paris Rive Gauche and Ivry-Port Nord.